Challenges and Solutions: The Experiences of Newly-Qualified Counsellors - FLORENCE ADEOTI, Yusuf; Okanlawon, Ayoade Ejiwale; Adesile, Imran Moshood (Journal of Education in Black Sea Region, 2021)
The emergence of the increases in the rate of different social vices among the adolescents in high schools calls for re-evaluation and updating of the existing operating counselling services in secondary schools' educational system. The study examined the challenges of the newly qualified school counsellors and the solution proffered. Six research questions were raised to guide the study. It adopted a mixed-method research approach. The results of the findings revealed that the lack of recognition of the role of counsellors in the school system was rated the highest among the challenges experienced by newly-qualified counsellors, non-referral of students who need to be sent to a counsellor by teachers was rated second. From the findings of the study of the awareness campaign on the importance of counselling through various media, the finding “more time should be allotted to practicum for counsellors in training” was the highest-rated as the solution to the challenges experienced by newly-qualified counsellors. The results obtained from the study also revealed that male counsellors might be experiencing different challenges from their female counterparts. The results of the study also show a significant difference in the challenges experienced by newly qualified counsellors based on school type. The findings revealed that there is a significant difference in the solution provided by newly qualified counsellors based on gender. The results also show that the solution provided by a counsellor from private schools does not differ from that of their public schools’ counterpart. Based on the findings of the study recommendations were made: government should provide public enlightenment programmes to parents, school administrators, teachers, and students through jingles, posters, billboards on the need to embrace counselling in the school system and make use of the facility. National University commission should revise the counsellor training programme and increase the period allocated for practicum for the counsellor in training in order to equip them for the tasks ahead. Keywords: challenges, solutions, experiences, newly qualified counsellors